Exploring Art - Mittler, Gene. (Macmillan/McGraw-Hill, 1992)
This illustrated title consists of eight essays on different aspects of the visual arts. It includes discussions of: the universal appeal of the visual arts; the basic elements that make up an artwork; the artists themselves; and the controversies that surround the art world.